1999
DOI: 10.1016/s0896-6273(00)80837-5
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Nociceptor Signaling Pathway Revealed in Protein Kinase C ε Mutant Mice

Abstract: There is great interest in discovering new targets for pain therapy since current methods of analgesia are often only partially successful. Although protein kinase C (PKC) enhances nociceptor function, it is not known which PKC isozymes contribute. Here, we show that epinephrine-induced mechanical and thermal hyperalgesia and acetic acid-associated hyperalgesia are markedly attenuated in PKCepsilon mutant mice, but baseline nociceptive thresholds are normal. Moreover, epinephrine-, carrageenan-, and nerve grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
311
1
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 423 publications
(330 citation statements)
references
References 43 publications
(2 reference statements)
14
311
1
4
Order By: Relevance
“…Moderate levels of expression have also been observed in adipocytes (Kobilka et al 1987) and spinal dorsal horn neurons (Nicholson et al 2005). The contribution of β 2 ARs to enhanced pain sensitivity is in line with results from previous studies demonstrating that epinephrine activates β 2 ARs located on primary afferent nociceptors and produces a hyperalgesic state in rats (Aley et al 2001;Khasar et al 1999a;Khasar et al 1999b;Khasar et al 2003). Additionally, common variants of the human β 2 AR gene, coding for differences in receptor expression and internalization, are associated with the development of TMJD (Diatchenko et al 2006).…”
Section: Comt Inhibition Increases Pain Behavior Via β 2 and β 3 Adresupporting
confidence: 85%
See 1 more Smart Citation
“…Moderate levels of expression have also been observed in adipocytes (Kobilka et al 1987) and spinal dorsal horn neurons (Nicholson et al 2005). The contribution of β 2 ARs to enhanced pain sensitivity is in line with results from previous studies demonstrating that epinephrine activates β 2 ARs located on primary afferent nociceptors and produces a hyperalgesic state in rats (Aley et al 2001;Khasar et al 1999a;Khasar et al 1999b;Khasar et al 2003). Additionally, common variants of the human β 2 AR gene, coding for differences in receptor expression and internalization, are associated with the development of TMJD (Diatchenko et al 2006).…”
Section: Comt Inhibition Increases Pain Behavior Via β 2 and β 3 Adresupporting
confidence: 85%
“…Recent studies have also identified a novel G i/s -independent mechanism whereby β 2 -and β 3 ARs activation can stimulate extracellular signal-regulated kinase (ERK; a type of MAPK) through a novel G i/s -independent mechanism (Azzi et al 2003;Cao et al 2000). Activation of β 2 ARs located on nociceptors has been shown to increase pain sensitivity via G s /adenylyl cyclase-driven protein kinase A-and protein kinase Cdependent pathways or via G i /MAPK-dependent pathways (Aley et al 2001;Khasar et al 1999a;Khasar et al 1999b). Upon stimulation, MAPKs regulate pain sensitivity through both transcriptional and non-transcriptional means (Obata and Noguchi 2004).…”
Section: Potential Signaling Mechanisms Whereby β 2/3 Receptors Mediamentioning
confidence: 99%
“…TRPV1 is acknowledged to exist in peripheral nerve terminals and can be sensitized by noxious heat over 43 °C. Additionally, some evidence also validates the contribution of TRPV1 to mechanotransmission after injuries in different conditions [42][43][44] .…”
Section: Discussionmentioning
confidence: 61%
“…Among these isoforms, PKCε is the most dominant in paclitaxel-induced neuropathy [18] . The activation of PKCε by other inflammatory mediators, such as bradykinin, has been proven to enhance the sensitivity of nociceptive neurons to heat stimulation [44] . Moreover, PKCε has been identified as the isoform of PKC that is likely closest to the onset of mechanical hyperalgesia [44] , which has been further validated by Hucho [46] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that epinephrine, acting on nociceptors, produces mechanical hyperalgesia through three different signaling pathways involving 1) cAMP-dependent PKA; 2) epsilon isozyme of PKC; and 3) extracellular signal-regulated kinases 1 and 2 (1,20). It has been demonstrated that the latter two pathways may also be initiated by the accumulation of cAMP (8,35).…”
Section: Discussionmentioning
confidence: 99%